The Strategies for Overcoming Cultural Untranslatability: The Case of Rabindranath Tagore’s Gora (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
The aim of this study is to show the cultural untranslatability of Rabindranath Tagore’s Gora (1910) by analyzing the translation of the novel by W.W Pearson. Both the source and translated texts are studied using the content analysis method keeping the central motif in mind. The present research paper finds that Gora is so deeply rooted in Bengali cultural issues, that the translator has faced immense difficulties in making those cultural substances familiar to the target audience. The translator has used some strategies for overcoming cultural untranslatability such as borrowing and naturalization, definition, addition, substitution, transliteration, cultural equivalence, omission, etc. but in spite of the use of these strategies, the translation remains at a distance from the source text. However, the translator has mostly employed one approach, but on rare occasions he has utilized more than one, for example, transliteration with addition or definition, to give the intended audience a clear understanding of what is being said.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 57-68